PENGARUH MACHIAVELLIAN, PEMBELAJARAN ETIKA DAN SIKAP ETIS AKUNTAN DAN MAHASISWA AKUNTANSI DI DENPASAR - Putu Wenny Saitri; Ni Nyoman Ayu Suryandari (Jurnal Ilmiah Akuntansi & Bisnis, 2017)
The responsibility of an accountant is to improve the integrity of financial statements that are expected to maintain their ethical stance. It is deemed important to examine the factors that influence the ethical behavior of accountants and accountants candidate is a student. This study replicates research Chrismastuti and Purnamasari (2004) who tried to predict the Machiavellian nature of the ethical behavior of accountants and accounting students. Machiavellian nature has long been described as an antisocial personality, which does not consider conventional morality and have low ideological commitment. Different with the other businesses in which the Machiavellian become commonplace and likely to be accepted, but in not in accounting profession. Accountants who have a high machiavellian nature will tend to accept the attitude or actions ethical dilemma. In addition, this study also uses the learning process in the subject of ethics to predict the behavior of an ethical accountant accounting students.Research was conducted on the entire university in Denpasar by respondents as many as 225 students and public accountant firm listed in Bali is 10 public accountant firm. Based on the formula slovin, then gained as much as 144 as the study sample. The technique of collecting data using questionnaires. Hypothesis testing results showed that the Machiavellian nature of the positive effect on the ethical attitudes of accounting students and accountants. While teaching ethics through ethical subjects had no effect on the ethical attitudes of students in accounting, and has no effect on Machiavellian nature of accounting students. Variable control in this study, gender, status, education and age had no effect on the ethical attitudes of students in accounting.Keywords: Machiavellian nature, Ethical Behavior, Learning Ethics, Professional Ethics Course Accountants